Analysis of Factors Affecting Demand for Kampung Chicken in Sidikalang - Siburian, Eben Haezer (Talenta Publisher, 2021)
The demand for kampung chicken meat has increased due to awareness to consume organic chicken meat. This research aims to find out the factors that influence the demand for chicken meat in Sidikalang City. This research was conducted in Sidikalang City from May until June 2021 with primary data processing. The research method used is multiple regression analysis and deliberate sampling. The results showed that the demand for chicken meat in Sidikalang city was influenced simultaneously by the price of chicken meat, the price of broiler chicken meat, family income, age, number of family members, education level and taste level. As conlusion that a significant influence on the demand for chicken meat is the family income with a confidence level of 95%.